(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article discusses issues of financing small businesses and private entrepreneurship. An economic analysis of financing small businesses and private entrepreneurs operating in the regions of the Republic of Uzbekistan, scientific proposals and practical recommendations are provided.